Viability of using olive stones as lightweight aggregate in construction mortars - del Río Merino, Mercedes; Guijarro Rodríguez, Javier; Fernández Martínez, Francisco; Santa Cruz Astorqui, Jaime (Revista de la Construcción. Journal of Construction, 2017)
This article presents the results of a research project which studies the feasibility of substituting -in cement mortars- the most commonly used lightweight aggregates in Spanish building constructions (i.e. expanded clay), by waste from the olive industry. Spain is the world’s largest producer of olive oil and olives, being therefore the main producer of olive-stone waste. These olive stones are currently used as biomass. To determine the viability of substitution, an experimental plan was designed. The objective of this plan was to add three different olive stone formats (entire, crushed and calcined) in cement mortars, using similar percentages additions as the ones used by the manufacturers of lightweight expanded clay mortars. From the results obtained it can be concluded that it is feasible to replace expanded clay by olive stones waste, obtaining mortars with lower densities, up to 30%, and improved compressive strength, up to 20% compared to lightweight expanded clay mortars.